Free-Floating Support Structure Generation. (November 2020) - Jang, Seongje; Moon, Byungjin; Lee, Kunwoo
Abstract: To print a 3D model with a 3D SLA printer, support structures are required for areas such as overhangs and islands. If there is no support structure below islands, the solidified material will float around in the vat. Further deposition in the areas will sink as well, resulting in a printing failure. This issue is called the floating island problem. To resolve this problem, two different approaches to detect support points have been developed. One is a slice-based approach that pre-slices the given 3D model and compares all sets of two consecutive layers; this is computationally inefficient. The other is a mesh-based approach that investigates primitives such as points, edges, and faces and samples the clusters; this method, however, tends to miss the local minimums and causes the problem. In this paper, we propose a novel method to create support structures. This method does not lead to the floating island problem, in contrast to the mesh-based approach. Besides, this method does not need pre-slice 3D models, nor does it need to compare slices. It first converts a 3D model into a geometric representation called a layered depth image (LDI). It then creates a directed graph from the LDI to describe the delivery path of self-support and identifies efficient support points to prevent material waste. The structures can be reinforced by considering the volume as well as the geometry of the model. They are also reinforced by adding connections between anchors to increase stability. This method is compared to well-known commercial slicers. The result proves that this method is computationally efficient and never causes floating island problems. Graphical abstract: Highlights: A method of generating support structures based on a layered depth-normal images (LDNI) is proposed. Support structures can be created without pre-slicing a given 3D model. A noisy surface does not lead to an excessive number of support points. To reduce material waste, support points are detected in a greedy manner. Support structures can be reinforced to hold the weight of a given 3D model.